Phytochemical profile, antioxidant, antibacterial, and DNA protection potential of Diospyros kaki L.f. from the Western Himalayas, India - Disha Upreti; Dheeraj Shootha; Chandni Joshi; Lalit M. Tewari; Geeta Tewari; Aabha Gangwar; Geetanjali Upadhayay; Vasundhra Lodhiyal; Anand Kumar; Naveen C. Pandey; Swati Kumari (Discover Applied Sciences)
Abstract Diospyros kaki L.f. (Family: Ebenaceae) is a medicinal plant traditionally used to treat various ailments, including cough, diabetes, gonorrhea, herpes, leucorrhea, and menorrhea. This study focuses on the ethanolic and methanolic extracts of D. kaki leaves (DKEL, DKML) and bark (DKEB, DKMB) to assess their chemical composition, antioxidant and antibacterial activities, as well as their DNA protection capabilities. Phytochemical analysis revealed that the methanolic leaf extract had the highest extraction yield, achieving an 18.07% extraction rate, highlighting its potential for further investigation. Flavonoids, phenolics, and tannins were abundant in the bark extract of D. kaki irrespective of the solvent. Total flavonoids and tannins were present in plenty in the DKMB while DKEB was rich in total phenolic content. Our findings demonstrated the potent antioxidant capacity of DKMB where the IC50 values were 16.81 µg/mL and 2.90 µg/mL when tested using DPPH and ABTS assays, respectively. The highest antibacterial activity was exhibited by DKMB against gram-positive bacteria including Bacillus subtilis, Bacillus megaterium, DKEB against Escherichia coli and DKEL against Serratia marcescens. Findings from disc diffusion method demonstrated the significant antibacterial properties of DKMB having minimum inhibitory concentration (MIC) values of 20 µg/mL. Activities were observed to be significantly and positively dependent on total content of flavonoids, phenolics and tannins. DKML exhibited potent DNA-protecting power at 15 µg/mL concentration. In conclusion, these results underscore D. kaki as a rich source of bioactive compounds, suggesting its potential use across various industries as a promising natural therapeutic agent.